Dispensation of Marriage in The Perspective of Children's Rights: Best Interest of The Children - Nabilah Luthfiyah Chusnida; Teddy Prima Anggriawan (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
Underage marriage with marriage dispensation is very influential on the lives of children and adolescents. The Convention on the Rights of the Child has determined that the best interest of the child is the primary interest in any action concerning the child. This study uses a normative juridical method based on a statutory approach. The purpose of this research is to find out the judge's considerations and what factors cause the rise of early marriage. This study concludes that the number of marriage dispensations in Indonesia continues to increase from 2016-2018, and is stagnant in 2019-2020. This figure increases because awareness of the meaning of marriage is reduced and many people in Indonesia think that adat must still be maintained. The high dispensation of marriage is caused by economic factors, pregnancy out of wedlock, and cultural factors. Thus, the judge assessed that the granting of a marriage dispensation had the best impact on the child in accordance with the theory of the best interests of the child. The implementation of the regulations that have been implemented still requires derivative regulations that regulate the basics of granting marriage dispensations in court. In order for the application for a marriage dispensation to be granted wisely, it is recommended to refer to Law Number 16 of 2019 concerning Marriage and PERMA Number 5 of 2019 concerning Guidelines for the Termination of Marriage Dispensation. So that judges avoid subjective considerations in adjudicating marital dispensation cases.